2017
DOI: 10.1038/srep45592
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway for amyloids self-assembly in aggregates at nanomolar concentration mediated by the interaction with surfaces

Abstract: A limitation of the amyloid hypothesis in explaining the development of neurodegenerative diseases is that the level of amyloidogenic polypeptide in vivo is below the critical concentration required to form the aggregates observed in post-mortem brains. We discovered a novel, on-surface aggregation pathway of amyloidogenic polypeptide that eliminates this long-standing controversy. We applied atomic force microscope (AFM) to demonstrate directly that on-surface aggregation takes place at a concentration at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 41 publications
5
57
0
Order By: Relevance
“…The quantitative analysis of the number and sizes of aggregates shown in Fig. 1b demonstrate that these parameters increase gradually over time, which is similar to our earlier results obtained for Aβ42 aggregation on mica surface 10 . To characterize the role of electrostatics in the aggregation of Aβ42 on POPC, we performed experiments in the presence of 150 mM NaCl.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The quantitative analysis of the number and sizes of aggregates shown in Fig. 1b demonstrate that these parameters increase gradually over time, which is similar to our earlier results obtained for Aβ42 aggregation on mica surface 10 . To characterize the role of electrostatics in the aggregation of Aβ42 on POPC, we performed experiments in the presence of 150 mM NaCl.…”
Section: Resultssupporting
confidence: 89%
“…We used time-lapse AFM to directly visualize the aggregation process of Aβ42 protein on supported lipid bilayers formed from 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-L-serine (POPS) using the approaches described in [10][11][12][13] . A solution of 10 nM Aβ42 was placed on top of the SLBs, assembled on the mica substrate, and imaged at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results demonstrated that the assembly of proteins into aggregates took place at a low protein concentrations, while no aggregation was detected in bulk solution (17). Importantly, time-lapse AFM experiments in liquid did not reveal fast mobility of molecules at the mica-liquid interface (17). These data were also in line with observations performed using time-lapse high-speed AFM (18,19).…”
Section: Main Textsupporting
confidence: 80%
“…AFM has been used to directly observe the accelerated aggregation of amyloid peptides and the alpha-synuclein (α-Syn) protein on mica surfaces. Results demonstrated that the assembly of proteins into aggregates took place at a low protein concentrations, while no aggregation was detected in bulk solution (17). Importantly, time-lapse AFM experiments in liquid did not reveal fast mobility of molecules at the mica-liquid interface (17).…”
Section: Main Textmentioning
confidence: 93%